Answer:
C
Step-by-step explanation:
Generate the first few terms using the explicit rule
[tex]a_{1}[/tex] = 14 - (9 × 1) = 14 - 9 = 5
[tex]a_{2}[/tex] = 14 - (9 × 2) = 14 - 18 = - 4
[tex]a_{3}[/tex] = 14 - (9 × 3) = 14 - 27 = - 13
[tex]a_{4}[/tex] = 14 - (9 × 4) = 14 - 36 = - 22
The first 4 terms in the sequence are
5, - 4, - 13, - 22
These are the terms of an arithmetic sequence with common difference d
d = - 4 - 5 = - 13 - (- 4) = - 22 - (- 13) = - 9
To obtain the next term in the sequence subtract 9 from the previous term
[tex]a_{n}[/tex] = [tex]a_{n-1}[/tex] - 9 with [tex]a_{1}[/tex] = 5